Editorial: safety of ustekinumab in pregnancy—are we there yet?. Issue 4 (28th January 2022) - Skejø, Cæcilie; Vestergaard, Thea; Julsgaard, Mette
LINKED CONTENT: This article is linked to Flanagan et al papers. To view these articles, visit https://doi.org/10.1111/apt.16739